(untitled) (Homoeopathy for All, 2023)
Background : The lumpy skin disease virus (LSDV), which is a member of the genus Capripoxvirus of the family Poxviridae, causes lumpy skin disease (LSD), a viral ailment. Cattle and water buffalo are affected by this transboundary illness, which is significant economically. Due to its fast spread and significant economic losses, World Organization For Animal Health (WOAH) added LSD in list of diseases that require notification. After seeing outbreaks in Jaipur[8][9] we conducted a study at Gaushala in Jaipur, Rajasthan and found positive results after homoeopathic medication. Methods: This article reviews a study that was carried out at Gaushala in Jaipur (Rajasthan), in which 200 cattle with lumpy skin disease were treated with four homoeopathic drugs i.e. Pulsatiila, Mer sol, Kali iod, and Silicea to determine the effectiveness of Results: The study was conducted on 200 cattles, out of which 75% (150) get relief from Merc sol, 14% (28) from Silicea, 6% (12) from Pulsatilla, 5% (10) from kali iod. Conclusion : The study concludes that homoeopathic medicines have potential in treatment of lumpy disease. As the study is conducted on one place so further such studies are needed.